Latte Grande, No Sprinkles: An Exploratory Observational Study of Customer Behaviour at Chapters Bookstores - Dixon, Christopher M.; McKechnie, Lynee (E.F.); Miller, Laura J.; Rothbauer, Paulette M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
While the dramatic growth of book superstores has been of great concern to public libraries, there has been little serious research about what people actually do in bookstores. How much are their behaviours like those that typically occur in libraries? To what extent are they different? To answer these questions an unobtrusive observational study is underway at three Chapters bookstores in two large Ontario cities.